2017
DOI: 10.1123/ijspp.2015-0540
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Circulating Cell-Free DNA During Aerobic Running Depend on Intensity and Duration

Abstract: Both duration and level of intensity were significantly associated with accumulation of cfDNA. The correlation with RPE and the high test-retest reliability suggest that cfDNA might be applicable as a marker to monitor individual training load for aerobic and intermittent exercises. Future randomized, controlled, longitudinal training studies will have to reveal the full potential of cfDNA as an exercise-physiology marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…CfDNA levels are known to increase during exercise and up to 8-fold rises have been reported following moderate aerobic running. 10 In agreement with our primary analysis, a vast number of analytes have been demonstrated to display comparable biological variation in healthy and diseased subjects. 19 This supports the applicability of cfDNA CVs and RCVs estimated from healthy subjects to cancer patients and possibly patients with other chronic illnesses as well.…”
Section: Discussionsupporting
confidence: 83%
“…CfDNA levels are known to increase during exercise and up to 8-fold rises have been reported following moderate aerobic running. 10 In agreement with our primary analysis, a vast number of analytes have been demonstrated to display comparable biological variation in healthy and diseased subjects. 19 This supports the applicability of cfDNA CVs and RCVs estimated from healthy subjects to cancer patients and possibly patients with other chronic illnesses as well.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, we assume that our cortisol dataset based on the measurement procedure with three time points (08:30 AM, 10:30 AM, and 12:30 PM) is not entirely comparable with the time points used previously [45]. Some studies have reported that cfDNA levels already increase with moderate PA below the level of the aerobic-anaerobic transition [26,28]. The results of the cfDNA AUCi posterior distributions suggest that such a association is also more likely in both teaching settings.…”
Section: A) B) C) D)mentioning
confidence: 94%
“…Based on plasma samples, the cfDNA is a well-established indicator of the activation of the innate immunity. Various studies have revealed that the innate immunity could be activated by both psychologically [21][22] and physiologically [23][24][25][26][27] stressful situations. In particular, the cfDNA has been proven to be highly sensitive to physical exercise as a stressor (see [27] for review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanism underpinning the increased release of cfDNA during exercise is poorly understood, it appears that cfDNA is primarily released from cells involved in immune function [119]. The magnitude of cfDNA concentration increases also appears proportional to both exercise intensity and duration [119,120], and the time course of these changes is remarkably transient, with cfDNA concentrations often returning to baseline within 24 h, even after highly exhaustive exercise [115]. As a result, cfDNA represents a potentially novel biomarker for fatigue and recovery in exercise [113,119,120].…”
Section: Section Summarymentioning
confidence: 99%